2008
DOI: 10.1097/01.hp.0000298927.60209.dd
|View full text |Cite
|
Sign up to set email alerts
|

The NORMAN phantom vs. the BOMAB phantom: are they different?

Abstract: This paper describes the implementation of the NORMAN phantom with the Human Monitoring Laboratory's Monte Carlo simulator, the problems that were encountered, and their solution. The NORMAN phantom has been compared with the reference man BOMAB phantom in three different whole body counting geometries: a scanning detector system (WBC1), and two stand-up whole body counters (WBC2, WBC3) that have different reference points for their counting geometry. The average agreement (taken over all energies) of the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…For the WHR no linear correlation was found. Similar results were observed by Kramer et al [18], which demonstrated that the linearity may differ for different counting systems and different source geometries. In conclusion, no parameter could be found to relate the counting efficiency to the body geometry.…”
Section: Correlation Between the Counting Efficiency And Trunk Volume...supporting
confidence: 88%
See 2 more Smart Citations
“…For the WHR no linear correlation was found. Similar results were observed by Kramer et al [18], which demonstrated that the linearity may differ for different counting systems and different source geometries. In conclusion, no parameter could be found to relate the counting efficiency to the body geometry.…”
Section: Correlation Between the Counting Efficiency And Trunk Volume...supporting
confidence: 88%
“…As previously reported [2,[18][19][20], it may not always be appropriate to describe the calibration factor to have a linear relationship to parameters such as body build index (BBI)-(weight/height) 1/2 -or body mass index (BMI)-(weight/height 2 )and also, it may not be the same for different counting geometries (flat bed, reclining chair, types of detectors used, and the detector position in respect to the person being measured, etc).…”
Section: Anatomical Parameterssupporting
confidence: 74%
See 1 more Smart Citation